Do plano de melhoramentos ao plano urbanístico: a contribuição das concepções que impactaram o pensamento urbano paulista - Toledo, Rodrigo Alberto [UNESP] (My University, 2012)
The present article intends to rank the main influences that Anhaia Mello had at the formulation of a paulista urbanistic thought. This way, it will be discussed the main issues raised at the period, which is between the first decades of the XX Century to the end of the 1950s, trying to foresee how they worked as engineers and architects to incorporate the urbanistic proposals from Europe and the United States. And then, we will present, on the first four sections of this article, the way points of view that effectively impacted the paulista urban thought of the first half of the XX century: Sanitarism, pendular conception between the Mesologic Theory and the Microbian Theory; the Historicist formulation of Camillo Sitte; Howard´s garden-town and the French experience. Our analyses were formulated having as a reference the broad systematization of bibliiography and documents performed at the Arquivo Histórico Municipal (Intermediário) de Araraquara (Historical Municipal Archive from Araraquara), consulations at the the books of the library of the biblioteca da Faculdade de Arquitetura e Urbanismo da USP (USP Architecture and Urbanism College) and at the Faculdade de Ciências e Letras da Unesp, Araraquara-SP( College of Sciences and Languages from Unesp, campus Araraquara). The analisys of the performed research show that two urbanistic torrents happened at Sao Paulo State happened with clear influences from the conceptions that led the urbanistic debates in the first half of the XX Century. Although these conceptions compose a painting of urban interventions at São Paulo city and noticeably in some inner cities, previously to the solidification of a whole proposition for the city that was later called of Directive Plan.

O presente artigo pretende elencar as influências na formulação de um pensamento urbanístico paulista. Dessa forma, discutiremos as questões levantadas no período, desde as primeiras décadas do século XX até o final da década de 1950, buscando apresentar as principais concepções urbanísticas do período que contribuíram na formação do arcabouço teórico utilizado por engenheiros e urbanistas em suas propostas de intervenções. Destarte, apresentaremos, nas quatro primeiras seções deste artigo, as concepções que efetivamente impactaram o pensamento urbano paulista até a primeira metade do século XX: Sanitarismo, concepção pendular: entre a Teoria Mesológica e a Teoria Microbiana; A formulação historicista de Camillo Sitte; A cidade-jardim de Howard e a experiência francesa. Nossas análises foram elaboradas a partir de ampla sistematização bibliográfica realizada no acervo da biblioteca da Faculdade de Arquitetura e Urbanismo da USP e da Faculdade de Ciências e Letras da Unesp de Araraquara, estado de São Paulo. As análises dos levantamentos sistematizados apontam que o pensamento urbanístico forjado no Estado de São Paulo sofreu influências das concepções que conduziram os debates dos urbanistas na primeira metade do século XX. Entretanto é de fundamental importância destacar que essas concepções compõem um quadro de intervenções urbanas na cidade de São Paulo e, visivelmente, em algumas cidades do interior paulista anteriores à solidificação de uma proposta interventora totalizante de cidade, denominada, posteriormente, de Plano Diretor.
Keywords: Urban thought; Urban planning; Democracy; Participation; Public policies; Pensamento urbano; Planejamento urbano; Camillo de Sitte; Sanitarismo; Cidade-jardim; Urbanismo francês